DETERMINATION OF CRITICAL THINKING AND INDEPENDENT LEARNING: ANALYSIS OF CONFIDENCE AND MOTIVATION - Humairatuz Zahrah; Kemas Imron Rosyadi (Dinasti International Journal of Education Management And Social Science, 2022)
In this study, the author raises various themes related to the factors that influence critical thinking and its impact on Independent Learning. This study is interesting to discuss because the author wants to see in depth the effect of Critical Thinking and Independent Learning on Self-confidence and Motivation, in this study the author uses library research methods. The results of this study illustrate that critical thinking is needed as intellectual capital in achieving educational goals. Besides that, motivation is also a crucial factor in the critical thinking process, because every element of education requires encouragement from both inside and outside to move optimally so that the regulations that have been set can be implemented optimally and of course have an impact on independent learning which is the reference for the ideal concept of education. at the moment. In the context of education, critical thinking is very influential on independent learning. Freedom of learning supports many innovations in the world of education, especially the progress of various educational institutions including schools or madrasas, by also forming teacher competencies. Teachers who are independent in teaching are aware of the needs of their students according to the environment and culture of the students.